Image Processing in the Woodworking Industry: Challenges, Solutions and Platforms - Molder, A.; Martens, O. (Elektronika ir Elektrotechnika, 2011)
Machine vision, automatic optical inspection and image processing has been used for quality control in electronics industry forseveral years. Many applications have been developed for security, packaging industries and elsewhere, but machine vision and imageprocessing is relatively new and underused area in the woodworking industry. Wood is very characteristic and although the applicationareas of image processing in woodworking industries are endless, the processing methods are rather complex. This paper describesbriefly an image processing applications mainly and currently used in woodworking industries nowadays, unsolved challenges of imageprocessing and possible solutions. Also benefits and performance aspects of real-time low-cost low-power embedded platforms, likeTexas Instruments OMAP processors with embedded ARM and DSP cores have been analyzed and discussed. Ill. 2, bibl. 10 (in English;abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.610